Prognostic Significance of SOCS3 in Patients With Solid Tumors: A Meta-Analysis - Zheng, Xia; Shao, Jie; Wei, Sihui; Gu, Yu; Qian, Jun (Frontiers in Surgery, 2022)
Background: The identification of reliable biomarkers for predicting disease recurrence and the survival of patients with cancer is of great importance. Numerous previous studies have revealed that the abnormal expression of suppressor of cytokine signaling 3 (SOCS3) was associated with patient outcomes. However, these results were inconsistent. The aim of the present study was to assess the prognostic value of SOCS3 in patients with solid tumors. Methods: Studies focusing on the prognostic value of SOCS3 in solid tumors were searched in the PubMed, Embase, Web of Science, and Scopus databases. We included studies that compared disease-free survival (DFS) and overall survival based on different levels of SOCS3. Other outcomes (e.g., Edmondson grading, tumor size, tumor vascular invasion, lymph node invasion, and distant metastasis) were also considered. The hazard ratio (HR)/risk ratio (RR) and corresponding 95% confidence interval (CI) were determined. Results: Twelve studies with 1,551 patients were included in this meta-analysis. The pooled analysis demonstrated that higher expression of SOCS3 was significantly associated with better disease-free survival (HR: 0.36, 95% CI: 0.17–0.77, P<0.001) and overall survival (HR: 0.45, 95% CI: 0.32–0.62, P<0.001) compared with low expression. Moreover, SOCS3 expression was closely correlated with the Edmondson grading (OR: 0.77, 95% CI: 0.61–0.98, P=0.033), vascular invasion (OR: 0.63, 95% CI: 0.52–0.78, P<0.001), and distant metastasis (OR: 0.73, 95% CI: 0.51–1.03, P=0.076). However, the levels of SOCS3 were not significantly associated with tumor size (OR: 0.85, 95% CI: 0.71–1.03, P=0.090) and lymph node invasion (OR: 0.73, 95% CI: 0.51–1.03, P=0.076). Conclusion: Increased SOCS3 expression in tumor mass was associated to better DFS and OS, suggesting it might be a novel and reliable biomarker for predicting the risk of cancer recurrence and mortality.